National cultures of buying organisations have a role in cross-cultural selling : industrial selling context - Rinne, Liisa (My University, 2022)
The objective of this thesis is to explore how national cultures of buying organisations are reflected in cross-cultural sales. With the sub-questions, the thesis answers how professional sellers perceive national cultures to influence organisational buying behaviour, how these perceptions correspond to Hofstede’s national cultural dimensions and how professional sellers adapt selling to the national cultural differences in organisational buying behaviour. The subject of the thesis is current as cross-cultural selling has increased, and in today’s global atmosphere, the influences of national cultures cannot be ignored. However, the existing research on the subject is scarce, and additional studies are required. The theoretical framework of the thesis is collected from various previous studies and connects the proposed influences of national culture to organisational buying behaviour to cross-cultural selling. Thus, the theoretical background presents previous findings on the national cultural dimensions, the suggested impacts of national culture on buying centres and buying process and how the cultural differences in organisational buying behaviour can influence professional selling process and tactics. The research data is qualitative and collected through semi-structured theme interviews based on the proposed synthesis. The six interviewees are professional sellers selling capital industrial goods internationally to other organisations. The collected research data is analysed utilising a network aspect to thematic analysis. The empirical research presents that professional sellers perceive national culture to reflect on multiple aspects of organisational buying behaviour to a differing degree. The professional sellers have perceived that the national culture of buying organisations contributes to professional selling in numerous ways. The most significant differences are found in the division of authority and decision-making of the buying centre. However, multiple other factors influence organisational buying behaviour and professional selling, and thus it can be challenging to determine the impact of national cultures. The empirical findings support the existing findings to a large extent. The profession sellers perceptions followed the findings of previous studies on how national cultures influence organisational buying behaviour. In addition, professional sellers adapted selling to most of the cultural differences in organisational buying behaviour. This supports the existing literature. However, the empirical findings are not in line with Hofstede’s national culture dimensions to a large extent. In addition, the empirical findings propose new contributions regarding, for example, how professional adapt to the cultural differences in buying centres’ attitudes towards innovations and the importance of rules. The findings of this study can be utilised in cross-cultural selling.

Tämä tutkimus pyrkii tarkastelemaan kuinka osto-organisaatioiden kansallinen kulttuuri vaikuttaa kulttuurien väliseen myyntiin. Tutkimuskysymyksien avulla tutkielma pyrkii vastaamaan kuinka ammattimyyjät mieltävät kansallisen kulttuurin vaikuttavan organisaatioiden ostokäyttäytymiseen, miten nämä havainnot vastaavat Hofsteden kansallisen kulttuurin dimensioita ja kuinka ammattimyyjät mukauttavat myynnin kansallisiin kulttuurieroihin organisaatioiden ostokäyttäytymisessä. Tutkimuksen aihe on ajankohtainen, koska kulttuurienvälinen myynti on lisääntynyt ja kansallisten kulttuurien vaikutusta ei voida jättää huomioimatta tämän päivän globaalissa ympäristössä. Kuitenkin nykyinen tutkimustieto aiheesta on vähäistä ja enemmän tutkimuksia aiheesta tarvitaan. Tämän tutkimuksen viitekehys on koostettu monista eri tutkimuksista ja se yhdistää ne yhtenäiseksi ehdotukseksi siitä, miten kansalliset kulttuurit voivat vaikuttaa organisaatioiden ostokäyttäytymiseen ja minkälaisia vaikutuksia tällä on kulttuurienväliseen myyntiin organisaatioiden välillä. Tutkimuksen teoreettinen tausta esittää tutkimustuloksia kansallisista kulttuuridimensioista, kansallisen kulttuurin vaikutuksista organisaatioiden ostoryhmään ja ostoprosessiin, sekä miten ostoryhmän kansallinen kulttuuri vaikuttaa myyntiprosessiin ja myyntitaktiikkoihin. Tutkimus on laadullinen ja tutkimusaineisto kerättiin puolistrukturoidulla teemahaastattelulla, joka perustui muodostettuun synteesiin. Kuusi haastateltavaa ammattimyyjää myyvät investointituotteita kansainvälisesti toisille teollisuuden alan organisaatioille. Kerätty aineisto analysoitiin hyödyntäen teema-analyysiä perustuen verkostonäkökulmaan. Empiiriset tutkimustulokset esittävät, että ammattimyyjät ovat huomanneet kansallisen kulttuurin vaikuttavan organisaatioiden ostokäyttäytymisen eri ulottuvuuksiin. Kansallisen kulttuurin vaikutuksen vahvuus vaihtelee eri organisaatioiden ostokäyttäytymisen piirteissä. Tutkimustuloksien mukaan kansallisen kulttuurin koettiin vaikuttavan erityisesti vallan jakautumiseen ostoryhmässä ja päätöksenteossa. Ammattimyyjät kokivat, että ostoryhmän kansallinen kulttuuri vaikutti myyntiin monin eri tavoin. Kansallisen kulttuurin vaikutusta oli kuitenkin vaikea arvioida, koska organisaatioiden ostoryhmään ja myyntiin vaikuttaa samanaikaisesti monia eri tekijöitä. Tutkimustulokset tukivat aiempia tutkimustuloksia laajasti vaikkakaan eivät kaikilta osin vahvistaneet Hofsteden kansallisen kulttuurin dimensioiden vaikutusta organisaatioiden ostokäyttäytymisen eroavaisuuksissa. Ammattimyyjien näkemykset kansallinen kulttuurin vaikutuksista organisaatioiden ostokäyttäytymiseen tukevat laajasti aiempia tutkimuksia. Lisäksi ammattimyyjät mukautuivat organisaatioiden ostokäyttäytymisen kulttuurieroihin. Tämä vahvisti aiempia tutkimustuloksia aiheesta. Lisäksi tutkimustulokset toivat lisätietoa siihen, miten ostoryhmän kansallinen kulttuuri voi vaikuttaa kulttuurienväliseen myyntiin, kuten miten ammattimyyjät mukautuvat ostoryhmän asenteisiin koskien innovaatioita ja sääntöjen tärkeyttä. Tämän takia tutkimustuloksia voi hyödyntää kulttuurien välisessä myynnissä.
Keywords: national culture, cross-cultural selling